Clinical characteristics and outcomes of acute community acquired pneumonia in children at a reference public hospital in Pernambuco State, Brazil (2010-2011) - Rita de Cássia Coelho Moraes de Brito; Talitha Coelho Moraes Guerra; Luciana de Holanda Lima Dornelas Câmara; Juliana Dias Pereira Gomes de Mattos; Maria Julia Gonçalves de Mello; Jaílson de Barros Correia; Norma Lucena Silva; Giselia Alves Pontes da Silva
Abstract Objectives: to describe the clinical characteristics and outcomes of acute community acquired pneumonia in children at a reference public hospital in Pernambuco State, Brazil (2010-2011) Methods: pneumonia case series of 80 children aged 28 days to 14 years old at Hospital da Restauração in Pernambuco, Brazil, from 2010 to 2011. Information was noted from medical files, and two comparison groups were created according to the severity of the disease, considering the presence of pleural effusion. Fisher or Mann-Whitney tests were used for comparative analyses. Results: severe pneumonia with pleural effusion was more frequent in children under five years of age (p=0,025), and was associated with longer period of fever (19 x 15 days) and coughing (17 x 13 days), when compared to non-complicated pneumonia cases. Six children (7,5%, 6/80) died, 50% before the fourth day of hospitalization (p=0,001). All deaths were from the pleural effusion group in children from the countryside (p=0,026). Conclusions: the severity of pneumonia in children attended at this hospital is related to younger children, and those transferred from the health units in the countryside, so, early diagnosis and medical intervention are limited by infrastructure and available resources for the health.